The fractions you have to add are 1/3 and -5/6
![(1)/(3)+(-(5)/(6))](https://img.qammunity.org/2023/formulas/mathematics/college/1c1sulmyhuz0c9jycagh9os6xr0iy76oqh.png)
The denominators are "3" and "6"
The common denominator between both numbers is 6.
6*1=6
3*2=6
Multiply 1/3 by factor 2 so that both fractions will have the same denominator
![(1)/(3)\cdot2=(1\cdot2)/(3\cdot2)=(2)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/x3dbq17w71ywc8suqq7gw9grhui7b0043q.png)
Now you can add both fractions
![(2)/(6)+(-(5)/(6))=(2)/(6)-(5)/(6)=(2-5)/(6)=-(3)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/cjh4ffg9gh1lr8dgv2m04wagslgtfuk0ys.png)
The result is not in its most reduced form, to siplify the fraction divide both the numerator and denominator by 3
![-(3)/(6)/3=-(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/eu7k4peurfoq3hgi064n87wneoq05dr83v.png)
The result is -1/2, in the number line: